Coagulation factor inhibitors in COVID‐19: From SARS‐CoV‐2 vaccination to infection. Issue 3 (14th April 2022) - Jacobs, Jeremy W.; Adkins, Brian D.; Walker, Shannon C.; Booth, Garrett S.; Wheeler, Allison P.
Abstract: Background: Recent reports have highlighted patients with COVID‐19 and vaccine recipients diagnosed with coagulation factor inhibitors. This is challenging. as severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection has been identified as a prothrombotic risk factor, with heparin treatment decreasing mortality. However, both infection and vaccination have been associated with immune‐mediated hematologic abnormalities, including thrombocytopenia, further rendering these groups at risk for both hemorrhagic and thrombotic events. Objectives: We sought to characterize the incidence and clinical findings of coagulation factor inhibitors in patients with COVID‐19 and vaccine recipients. Methods: We queried the US Centers for Disease Control and Prevention's Vaccine Adverse Event Reporting System (VAERS), a publicly accessible database, for reports of potential bleeding episodes or coagulation disturbances associated with SARS‐CoV‐2 vaccination. We performed an additional comprehensive literature review to identify reports of SARS‐CoV‐2 infection or vaccination‐associated coagulation factor inhibitors. Results: VAERS data showed 58 cases of coagulation factor inhibitors, suggesting a rate of 1.2 cases per 10 million doses. A total of 775 articles were screened and 15 were suitable for inclusion, with six reports of inhibitors after vaccination and nine reports of inhibitors after infection. Inhibitor specificity for factor VIII was most common. Among reported cases, two patients expired due to hemorrhage, one following infection and one following vaccination. Conclusion: The incidence of coagulation factor inhibitors in patients with SARS‐CoV‐2 vaccination and infection appears similar to the general population. Nonetheless, given the importance of heparin therapy in treating hospital patients, recognition of inhibitors is important.